Texture from Touch - Drucker, Steven (Natural Computation, 2015)
Texture from touch refers to the processing of information about surface material and microgeometry obtained from tactile exploration. Though textural information can be obtained both visually (Heller 1989) and auditorily (Lederman 1979), touch yields much finer and more complex textural information than do the other sensory modalities.